Silicon oxycarbide (SiOC) ceramic microspheres – Structure and mechanical properties by nanoindentation studies. Issue 9 (15th June 2019) - Szymanski, Witold; Lipa, Sebastian; Fortuniak, Witold; Chojnowski, Julian; Pospiech, Piotr; Mizerska, Urszula; Slomkowski, Stanislaw; Nyczyk-Malinowska, Anna; Hasik, Magdalena
Abstract: The mechanical properties of silicon oxycarbide (SiOC) microspheres were studied using the nanoindentation technique. The nanoindentation process was also simulated by the finite element modeling (FEM) method. The microspheres were prepared by the ceramization of polysiloxane microspheres obtained by processing the aqueous emulsion of polyhydromethylsiloxane (PHMS). The preceramic microspheres consisted of cross-linked polysiloxane. Their flexible structure enabled obtaining fracture-free solid SiOC microspheres from the pyrolysis process carried out at temperatures up to 1400 °C. The hardness and elastic modulus of the microspheres are high, reaching up to 15.9 GPa and 144.9 GPa, respectively. Using 1, 3-divinyltetramethyldisiloxane (DVTMDS), divinylbenzene (DVB) and 1, 3, 5, 7-tetravinyltetramethylcyclotetrasiloxane (V4) as cross-linkers in the preparation of the preceramic microspheres yields ceramic particles with an enhanced content of carbon-silicon bonds, as well as particles with an increased amount of segregated free carbon. The particles possessing an enhanced content of silicon-bonded carbon exhibit the largest hardness and elastic modulus. The microspheres were also characterized by 29 Si MAS NMR and Raman spectroscopies, XRD, SEM and elemental analysis.